MULTI-ASPECT CHARACTER AND UNITY OF THE TOURIST BRAND OF A CITY (BY THE EXAMPLE OF KAZAN CITY) - S. E. Ivanov (Russian Journal of Economics and Law)
Branding of territories as a sphere of scientific interests and practical research is a relatively new direction of modern marketing. The article presents a brief review of the experience of cities' promotion. Special attention is paid to the issue of tourist positioning of territories in the international market. The author summarizes the experience of promotion of Kazan city as a tourist destination, and presents his own opinion on its tourist brand.